A meta-analysis of gemcitabine containing chemotherapy for locally advanced and metastatic pancreatic adenocarcinoma - Hu, Jing (BioMed Central, 2011)
BACKGROUND: The objectives of the present study are to investigate the efficacy and safety profile of gemcitabine-based combinations in the treatment of locally advanced and metastatic pancreatic adenocarcinoma (LA/MPC). METHODS: We performed a computerized search using combinations of the following keywords: "chemotherapy", "gemcitabine", "trial", and "pancreatic cancer". RESULTS: Thirty-five trials were included in the present analysis, with a total of 9,979 patients accrued. The analysis showed that the gemcitabine-based combination therapy was associated with significantly better overall survival (OS) (ORs, 1.15; p = 0.011), progression-free survival (PFS) (ORs, 1.27; p < 0.001), and overall response rate (ORR) (ORs, 1.58; p < 0.001) than gemcitabine monotherapy. Similar results were obtained when the gemcitabine-fluoropyrimidine combination was compared with gemcitabine, with the OS (ORs, 1.33; p = 0.007), PFS (ORs, 1.53; p < 0.001), and ORR (ORs 1.47, p = 0.03) being better in the case of the former. The OS (ORs, 1.33; p = 0.019), PFS (ORs, 1.38; p = 0.011), and one-year survival (ORs, 1.40; p = 0.04) achieved with the gemcitabine-oxaliplatin combination were significantly greater than those achieved with gemcitabine alone. However, no survival benefit (OS: ORs, 1.01, p = 0.93; PFS: ORs, 1.19, p = 0.17) was noted when the gemcitabine-cisplatin combination was compared to gemcitabine monotherapy. The combinations of gemcitabine and other cytotoxic agents also afforded disappointing results. Our analysis indicated that the ORR improved when patients were treated with the gemcitabine-camptothecin combination rather than gemcitabine alone (ORs, 2.03; p = 0.003); however, there were no differences in the OS (ORs, 1.03; p = 0.82) and PFS (ORs, 0.97; p = 0.78) in this case. CONCLUSIONS: Gemcitabine in combination with capecitabine or oxaliplatin was associated with enhanced OS and ORR as compared with gemcitabine in monotherapy, which are likely to become the preferred standard first-line treatment of LA/MPC.